2021
DOI: 10.3389/fmats.2021.794051
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Source Starvation of a Sulfate-Reducing Bacterium–Elevated MIC Deterioration of Tensile Strength and Strain of X80 Pipeline Steel

Abstract: It is known that starved sulfate-reducing bacterial biofilms corrode carbon steel more aggressively because they use electrons from elemental iron oxidation as an alternative source of energy. This work used carbon source starvation to vary MIC (microbiologically influenced corrosion) severity for studying subsequent MIC impacts on the degradation of X80 carbon steel mechanical properties. X80 square coupons and dogbone coupons were immersed in ATCC 1249 culture medium (200 ml in 450-ml anaerobic bottles) inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Most MIC studies focused on MIC pinhole leaks (Chandra et al, 2019;Dao et al, 2021). More attention should be paid to deterioration of mechanical properties of steels, including reductions of tensile strength and strain (Li et al, 2021a;Li et al, 2022). Such deteriorations can lead to catastrophic structural failures if not mitigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most MIC studies focused on MIC pinhole leaks (Chandra et al, 2019;Dao et al, 2021). More attention should be paid to deterioration of mechanical properties of steels, including reductions of tensile strength and strain (Li et al, 2021a;Li et al, 2022). Such deteriorations can lead to catastrophic structural failures if not mitigated.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the presence of corrosive Bacillus megaterium bacterium decreased the mechanical properties such as yield stress, ultimate strength and elongation of an Al-Cu alloy ( Yousaf et al, 2015 ). Recently, it was found that moderately starved D. vulgaris biofilm degraded ultimate tensile strength and ultimate tensile strain of X80 carbon steel more than those with the biofilm without carbon source starvation because starvation made SRB sessile cells more eager to harvest electrons from Fe(0) via EET ( Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…X80 carbon steel is widely used in many industries because of its low cost and ease of fabrication ( López-Celvera et al, 2018 ; Zhang et al, 2019 ; Pereira et al, 2021 ; Tian and Pan, 2021 ). However, X80 steel pipelines may suffer from both MIC and mechanical property degradation caused by MIC ( Alamri, 2020 ; Liu et al, 2022 ; Fu et al, 2022 ; Wasim and Djukic, 2022 ). This study investigated the effects of SRB sessile cell growth on MIC and the subsequent mechanical property degradation of X80 pipeline steel.…”
Section: Introductionmentioning
confidence: 99%